Spontaneous Disappearance of Two Asymptomatic Arachnoid Cysts in Two Different Locations - Cokluk, C; Senel, A; Celik, F; Ergur, H (Georg Thieme Verlag KG, 2003)
We report two children with asymptomatic arachnoid cysts which resolved spontaneously without any surgical intervention and history of major head and body trauma. The first child was a 10-year-old boy with an arachnoid cyst in the right sylvian fissure. The second child was a 1-year-old girl with a right cerebral convexity arachnoid cyst. Both of them were asymptomatic. Arachnoid cysts spontaneously disappeared within 2 years following initial diagnosing. There was no major head and body trauma except usual home, school and sports activity. We speculated that the cysts ruptured into cerebrospinal fluid circulation by the mechanical effects of some forced activities to the brain tissue and cyst, such as excessive breathing, coughing and sport activities. These factors may change the balance between intracystic and pericystic pressure and facilitate the rupturing of the cyst into subdural, subarachnoid and intraventricular spaces. These cases demonstrate that neurosurgical intervention of asymptomatic arachnoid cysts is not absolutely indicated in the paediatric age group. Close follow up with computerized tomography (CT) and magnetic resonance imaging (MRI) is a treatment option in the patient with arachnoid cysts located in the middle cranial fossa and cerebral convexity.
Keywords: Arachnoid Cysts; Asymptomatic Arachnoid Cysts; Cerebral Convexity; Spontaneous Disappearance